Research on the Impact of Electronic Word-of-Mouth (EWOM), User-Generated Content and Subjective Norm on the Intention to Purchase Vegan Cosmetics of Gen Z Women Through Social Media Platforms in Vietnam - Tran, Pham Huyen Trang (International Journal of Advanced Multidisciplinary Research and Studies, 2025)
International Journal of Advanced Multidisciplinary Research and Studies; 5(2); pp: 583-587